1981
DOI: 10.1136/gut.22.3.207
|View full text |Cite
|
Sign up to set email alerts
|

Hyperplasia of the exocrine pancreas after small bowel resection in the rat.

Abstract: SUMMARY The effect of a 90% small bowel resection on the exocrine pancreas was investigated over a three month period in adult Wistar rats. Control animals underwent a sham-resection consisting of a transection and reanastomosis of the small intestine. After jejunoileal resection, the wet weight of the gland increased significantly (52%) from the 15th day. The The first group (54 rats) served as sham-resected control animals and the second group (48 rats) underwent a 90 % resection of the small bowel. OPERAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…Associations between changes in the intestine and pancreas have been reported in previous studies. Haegel et al (1981) found that massive resection of the small intestine in rats led to exocrine pancreas hyperplasia. Many studies have addressed the effects of gut hormones on pancreatic hypertrophy and hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Associations between changes in the intestine and pancreas have been reported in previous studies. Haegel et al (1981) found that massive resection of the small intestine in rats led to exocrine pancreas hyperplasia. Many studies have addressed the effects of gut hormones on pancreatic hypertrophy and hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…We measured DNA and protein levels in pancreas, because ratios of DNA and proteins to equivalent volumes of pancreatic tissues are generally indicative of cellular hypertrophy and hyperplasia (Haegel et al 1981). Protein amount per 100 mg pancreas tissue was similar among the three groups (Fig.…”
Section: Effects Of Rygb On Pancreas Hyperplasiamentioning
confidence: 99%
“…Clearly this effect could just be an example of non-specific surgically-induced hyperplasia Significance versus control: ** = P <0.001, * = P <0.002. predisposing to carcinogenesis, but the fact that no increase in acidophilic foci was observed after small bowel resection despite a doubling of pancreatic weight is not entirely consistent with this view. The hyperplastic response of the pancreas to a 90% enterectomy is relatively short-lived (Haegel et al, 1981) and may have been inadequate to promote carcinogenesis; others have shown that a minimal threshold level of essential fatty acid in the diet is required to permit tumours to develop in rats given azaserine (Roebuck et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…4). Further support for this suggestion is found in the recent report that hyperplasia occurs in the pancreas when 90% of the small bowel is resected (Haegel et al 1981), a procedure which reduced significantly the amount of amylase in the pancreas. The effect of carbachol, both on [6-3H]thymidine incorporation and amylase secretion (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Quiescent (Go) cells in the exocrine pancreas can be stimulated to divide by a variety of trophic gastrointestinal hormones (Johnson, 1976), by cessation of ethionine treatment (Fitzgerald, Vinijchaikul, Carol & Rosenstock, 1968), by duct ligation (Hultquist, Karlsson & Hallner, 1979), by trypsin inhibitor (Melmed, El-Aaser & Holt, 1976) and by resection of the small bowel (Haegel, Stock, Marescaux, Petit & Grenier, 1981). The role of the autonomic nervous system in th-regulation ofcell division has not been studied in any great detail but has been considered to be less important than hormonal influences (Barrowman, 1975).…”
Section: Introductionmentioning
confidence: 99%